One-step hydrothermal fabrication of AgInS2/SnIn4S8 nanocomposite with enhanced visible-light-activated photocatalytic activity - Zhong Fei; Zhu Zong Qiang (E3S Web of Conferences)
In this experiment, AgInS2/SnIn4S8 materials were prepared via one-step hydrothermal method using silver chloride, the indium trichloride, stannic chloride and thioacetamide as source of silver, indium, tin and sulfur sources, respectively. The structure, content and optical property of the as-synthesized AgInS2/SnIn4S8 nanocomposite were investigated by powder Xray diffraction, energy dispersive X-ray spectroscopy, field emission scanning electron microscopy. The ratio of AgInS2 to SnIn4S8 was optimized. When the molar amount of AgInS2 to SnIn4S8 is 0.6, AgInS2/SnIn4S8 composite photocatalyst shows the highest photocatalytic activity for degrading 2-nitrophenol (2NP) due to large absorption range and visible-light response. AgInS2/SnIn4S8 composites not only can degrade 2NP and tetracycline, but also had good mineralization efficiency for pharmaceutical industry wastewater.